Effects of acute and chronic zinc exposure on steroid hormone receptor expression in the lined seahorse, Hippocampus erectus. Issue 3 (3rd February 2019) - Han, Xue; Li, Chunyan; Qin, Geng; Zhang, Bo; Wang, Xin; Lin, Qiang
Abstract : The element zinc (Zn) can elicit a variety of physiological responses in animals, particularly through its effects on steroid hormone receptor expression. Here, we evaluated the effects of Zn on the expression profiles of steroid hormone receptors in the lined seahorse, Hippocampus erectus, following experimental acute and chronic Zn exposure. Complex response patterns were observed; however, steroid hormone receptor expression in liver and kidney following 12‐day Zn injection (acute exposure) differed significantly from the control treatments. Apparent effects on hepatic lipid metabolism and osmotic regulation in the kidney need detailed investigation. Furthermore, 49‐day (chronic) waterborne Zn exposure produced a significant decrease in both estrogen receptor (ER) expression levels and estradiol concentrations. In additional, chronic exposure led to a substantial reduction of hepatic adipose cells, implying that Zn may regulate hepatic lipid metabolism via ER and estradiol. Our study demonstrated the effects of both acute and chronic Zn exposure on expression patterns of steroid hormone receptors, which will contribute to understanding the mechanism of Zn‐induced hepatic lipid metabolism and other physiological responses in seahorses.